The effect of lithium carbonate on the ultrastructural organization of cells of hepatocarcinoma-29 in the dynamics of cultivation (Experimental biology, 2020)
The theme of the study is an actual direction of modern experimental Oncology – the problem of studying the influence of inducers of cell death on ultrastructural changes in tumor cells that contribute to the development of apoptosis. The aim of this work was to study the ultrastructural organization of hepatocarcinoma-29 cells under the influence of lithium carbonate in the dynamics of their cultivation.        The scientific significance and novelty of the work is to obtain new data on the ultrastructural organization of hepatocarcinoma cells under the influence of lithium carbonate. The novelty of this study is to identify consistent changes in the content and structure of cytoplasmic organelles of hepatocarcinoma-29 cells in the dynamics of cultivation with the introduction of lithium carbonate.         The practical significance of the work lies in the possibility of using the obtained data for the development of targeted therapy of hepatocarcinoma by the combined use of lithium carbonate and cytostatics, which will simultaneously involve various cellular signaling pathways for the stimulation of apoptosis and autophagic cell death. The work was performed on the culture of hepatocarcinoma cells -29 using light and electron microscopy.         Changes in the volume and numerical density of cytoplasmic organelles of G-29 cells in the dynamics of cultivation under the influence of lithium carbonate were revealed. It is shown that carbonate has a damaging effect on the cells of GA-29, which increases in the dynamics of cultivation. There is a decrease in the volume density of mitochondria, tanks of the granular endoplasmic network, free polysomal complexes, while increasing the volume density of autophagosomes, autolysosomes and lysosomes. The data obtained indicate that lithium carbonate contributes to the reduction of energy and synthetic functions of GA-29 cells, the development of catabolic processes in them and the launch of cell death processes.         The data obtained make a significant contribution to cell biology, Cytology and histology, as well as Oncology. The practical significance of the results is that on the basis of the identified ultrastructural changes in hepatocarcinoma cells under the influence of lithium carbonate, it is possible to develop approaches to targeted therapy of this type of cancer.          Key words: hepatocarcinoma-29, ultrastructure, lithium carbonate